Determination of Price and Service Quality on Purchasing Decisions in the Jurnal Ilmu Multidisiplin - Ridwan, Muhammad; Sitti Rizki Mulyani (Dinasti Publisher, 2023)
This research discusses determination of price and service quality on purchasing decisions in the jurnal ilmu multidisiplin. Where the price in a journal is reasonable and can be found in a journal. The quality of service in journals includes the responsiveness of journal managers, journal admins so that the review process. This research uses quantitative methods, with a population of 90 authors and a sample of 40 authors who have published their articles in multidisciplinary science journals. The sampling method uses simple random sampling and processes primary data using SPSS version 27. The measurement scale uses a likert scale of one to five. The tests carried out are t-test, f-test and coefficient of determination test. The results of this study are: 1) Price affects the Purchasing Decision in the Journal of Multidisciplinary Science partially; 2) Service Quality affects Purchasing Decisions in Multidisciplinary Science Journals partially; and 3) Price and Quality of Service affect purchasing decisions in multidisciplinary science journals simultaneously.